2018
DOI: 10.3390/v10110612
|View full text |Cite
|
Sign up to set email alerts
|

Viroid Diseases in Pome and Stone Fruit Trees and Koch’s Postulates: A Critical Assessment

Abstract: Composed of a naked circular non-protein-coding genomic RNA, counting only a few hundred nucleotides, viroids—the smallest infectious agents known so far—are able to replicate and move systemically in herbaceous and woody host plants, which concomitantly may develop specific diseases or remain symptomless. Several viroids have been reported to naturally infect pome and stone fruit trees, showing symptoms on leaves, fruits and/or bark. However, Koch’s postulates required for establishing on firm grounds the vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 91 publications
(133 reference statements)
0
16
0
Order By: Relevance
“…Although the FHVd-LR structural features are closer to the VL-satRNA of LTSV and to cscRNAs than to viroids, we are unable to predict the biological nature of this novel Vd-LRNA from fig. Only bioassays may answer the specific question of whether FHVd-LR is able to replicate autonomously and systemically infect fig (Di Serio et al, 2018a). In this respect, experiments to test the transmission of FHVd-LR to virus-free fig plants by grafting and slash-inoculation of RNA preparations enriched in Vd-LRNAs and of in vitro-generated dimeric head-to tail transcripts are ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the FHVd-LR structural features are closer to the VL-satRNA of LTSV and to cscRNAs than to viroids, we are unable to predict the biological nature of this novel Vd-LRNA from fig. Only bioassays may answer the specific question of whether FHVd-LR is able to replicate autonomously and systemically infect fig (Di Serio et al, 2018a). In this respect, experiments to test the transmission of FHVd-LR to virus-free fig plants by grafting and slash-inoculation of RNA preparations enriched in Vd-LRNAs and of in vitro-generated dimeric head-to tail transcripts are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, experiments to test the transmission of FHVd-LR to virus-free fig plants by grafting and slash-inoculation of RNA preparations enriched in Vd-LRNAs and of in vitro -generated dimeric head-to tail transcripts are ongoing. Slash-inoculated plants were negative by RT-PCR and northern blot assays one and two months post-inoculation, but such bioassays in woody hosts may require longer times for systemic infection ( Di Serio et al, 2018a ).…”
Section: Discussionmentioning
confidence: 99%
“…PLMVd is the only viroid shared by all five nectarine trees that displayed three leaf disease phenotypes (asymptomatic, bleached, and chlorotic mottle) in this study. Some studies have shown that PLMVd infection can be associated with albinism (peach calico, PC) and green mosaic symptoms, and revealed a close association between the albino phenotype and variants containing an insertion of 12–14 nt, folding into a hairpin capped by a U-rich loop in the proposed PLMVd branched secondary structure 21,35 . It is worth noting that we did not find this 12–14 nt insertion in this study.…”
Section: Discussionmentioning
confidence: 99%
“…(Hataya et al, 2017;Vamenani et al, 2019). HSVd infection in most of these hosts is symptomless but other diseases have been identified in fruit trees associated with diverse isolates of this viroid (Di Serio et al, 2018).…”
Section: Iscovery Hos Ts and Symp Tomatologymentioning
confidence: 99%
“…(Hataya et al, 2017; Vamenani et al, 2019). HSVd infection in most of these hosts is symptomless but other diseases have been identified in fruit trees associated with diverse isolates of this viroid (Di Serio et al, 2018). In particular, cachexia in citrus (Semancik et al, 1988) and fruit diseases in trees of the genus Prunus : plum and peach (Sano et al, 1989) (Figure 1c), apricot (Amari et al, 2007) (Figure 1d), and sweet cherry (Xu et al, 2017).…”
Section: Discovery Hosts and Symptomatologymentioning
confidence: 99%